“The Role of a Yoruba Traditional Leaf in a Fermented Food Technology (Nauclea Latifolia, Sarcocéphalus Latifolius): Shedding Light on African Accuracy of Implicit Knowledge and Technologies" - Aimé, Segla Dafon; Simon, Akpona (Advances in Social Sciences Research Journal, 2018)
Starting from the foundational archaeology of concepts in language and cognition of an archaic fermented food technology in a society of oral, we try to demonstrate the accuracy of implicit traditional knowledge. Semantics and concepts are here cultural traces of hidden knowledge. The phytochemical analysis of the leaf which serves as food package shows it as well. And thus, we argue that Africa must “museumize” its ancient technological practices, yet at the same time, start with the said practices, in view of establishing a foundation for the much needed innovation in African societies.